2014
DOI: 10.1016/j.orcp.2012.12.004
|View full text |Cite
|
Sign up to set email alerts
|

Patient and physician characteristics associated with the provision of weight loss counseling in primary care

Abstract: Background A variety of physician and patient characteristics may influence whether weight loss counseling occurs in primary care encounters. Objectives This study utilized a cross-sectional survey of primary care patients, which examined patient characteristics, physician characteristics, and characteristics of the physician-patient relationship associated with weight loss counseling and recommendations provided by physicians. Participants Participants (N=143, mean age=46.8 years, mean BMI=36.9 kg/m2, 65%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
27
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 22 publications
(43 reference statements)
3
27
2
Order By: Relevance
“…Considering the increased frequency that these PCPs see their patients, specialty societies for paediatricians [53] and OB/GYNs [54] have a great opportunity and responsibility to insure their care providers are delivering consistent, impactful messages regarding the promotion of healthy weight-related behaviours. Our findings that female PCPs were significantly more likely to agree with personal belief statements are consistent with previous research highlighting differences in the weight-related counselling practices of male and female physicians [25]. Others have found that female PCPs are more knowledgeable about physical activity and healthy BMI guidelines [55], and more likely to counsel and refer patients for weight related treatment than males [25].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Considering the increased frequency that these PCPs see their patients, specialty societies for paediatricians [53] and OB/GYNs [54] have a great opportunity and responsibility to insure their care providers are delivering consistent, impactful messages regarding the promotion of healthy weight-related behaviours. Our findings that female PCPs were significantly more likely to agree with personal belief statements are consistent with previous research highlighting differences in the weight-related counselling practices of male and female physicians [25]. Others have found that female PCPs are more knowledgeable about physical activity and healthy BMI guidelines [55], and more likely to counsel and refer patients for weight related treatment than males [25].…”
Section: Discussionsupporting
confidence: 91%
“…Our findings that female PCPs were significantly more likely to agree with personal belief statements are consistent with previous research highlighting differences in the weight-related counselling practices of male and female physicians [25]. Others have found that female PCPs are more knowledgeable about physical activity and healthy BMI guidelines [55], and more likely to counsel and refer patients for weight related treatment than males [25].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Dutton et al. () also found that a higher BMI (>35 kg/m 2 ) was associated with receiving more frequent weight loss counseling. According to our findings, it was evident that the degree of obesity was a pertinent factor for prescribing medication.…”
Section: Discussionmentioning
confidence: 95%
“…Some providers feel they lack the knowledge and resources to provide nutrition or weight loss advice (Kolasa and Rickett, 2010; Puhl and Heuer, 2009). Physician and patient characteristics may also play a role in who received weight loss advice; Dutton et al found that female physicians were more likely to provide weight loss advice (Dutton et al, 2014). Unfortunately, even health professionals have been found to carry implicit biases and negative attitudes regarding those who are obese, which may prevent them from initiating weight loss advice (Puhl and Heuer, 2009; Schwartz et al, 2003; Teachman and Brownell, 2001).…”
Section: Discussionmentioning
confidence: 99%